1998
DOI: 10.1002/ana.410440111
|View full text |Cite
|
Sign up to set email alerts
|

Small‐fiber sensory neuropathies: Clinical course and neuropathology of idiopathic cases

Abstract: We describe the clinical features, natural history, and neuropathology of 32 patients presenting with "burning feet," for whom no specific cause was identified. All had neuropathic pain in the feet and morphological abnormalities of cutaneous innervation in skin obtained using punch biopsy. Most (29) had an abnormal sensory examination. All had normal strength, proprioception, tendon reflexes, and nerve conductions. Two clinical patterns were apparent, based on natural history and spatial distribution of cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
214
5
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(236 citation statements)
references
References 25 publications
16
214
5
1
Order By: Relevance
“…Definitions that require electrophysiologic studies (eg, nerve conduction studies), 23 expensive equipment (eg, computer-assisted sensory examination), 24 or invasive testing (eg, skin or nerve biopsy) 15 make large studies impractical. Definitions that require symptoms (eg, the Michigan Diabetes Neuropathy Score) 25,26 exclude large numbers of people with asymptomatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitions that require electrophysiologic studies (eg, nerve conduction studies), 23 expensive equipment (eg, computer-assisted sensory examination), 24 or invasive testing (eg, skin or nerve biopsy) 15 make large studies impractical. Definitions that require symptoms (eg, the Michigan Diabetes Neuropathy Score) 25,26 exclude large numbers of people with asymptomatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a variety of lower extremity complaints such as leg cramps, restless legs syndrome, and nonspecific leg pains can result from neuropathy. 15 An association between peripheral neuropathy and lower extremity ulcers, cellulitis, and amputations has not been excluded.…”
mentioning
confidence: 99%
“…Before the development of anti-PGP9.5 antibodies, visualization of unmyelinated C-fibres and thinly myelinated Aδ-fibres required analysis of a nerve biopsy with electron microscopy. The availability of skin biopsy prompted the recognition of SFN as a distinct clinical entity 117 . Furthermore, skin biopsy has enabled investigation of the innervation of autonomic structures, such as sweat glands, hair follicles and arteriovenous anastomosis, in autonomic neuropathies [118][119][120] .…”
Section: Box 1 | Quantitative Sensory Testingmentioning
confidence: 99%
“…By this fibre density can be readily quantified, with reported interobserver agreement as high as 96%. [40] Lindberger et al [41] has reported that levels of both substance P and calcitonin gene related peptide (CGRP) are reduced in skin biopsies from diabetic patients before clinical or neurophysiologic evidence of neuropathy. Levy et al [42] showed that there was a progressive loss in the number and area innervated by CGRP positive nerve fibres when normal subjects were compared with diabetic patients with clinical evidence of neuropathy.…”
Section: Tests For Autonomic Functionmentioning
confidence: 99%